Experience with using fosfestrol for treating metastatic castrate-resistant prostate cancer in resource-limited setting - Kalaiyarasi, Jayachandran Perumal; Radhakrishnan, Venkatraman; Ganesan, Trivadi S; Raja, Anand; Ganesan, Prasanth; Dhanushkodi, Manikandan; Sagar, Tenali Gnana (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Fosfestrol is a low-cost estrogen analog that is useful in the management of metastatic prostate cancer in resource-challenged settings. It acts by altering the pituitary axis, adrenal secretion, and 5-alpha reductase activity. Patients and Methods: The outcomes of metastatic castration-resistant prostate cancer patients treated with fosfestrol in our center between June 2012 and December 2015 were analyzed retrospectively. Fosfestrol was given orally at a dose of 120 mg thrice daily. Event was defined as the discontinuation of fosfestrol due to tumor progression or drug toxicity or death due to any cause. The event-free survival (EFS) and overall survival (OS) were calculated by the Kaplan–Meier method. Results: The analysis included 47 patients with a median age of 65 years. Initial Gleason score was available for 41 of 47 patients, of which 17% (7), 39% (16), and 44% (18) were low risk, intermediate risk, and high risk, respectively. The most common site of metastasis was bone (98%). Of 47 patients, 32 (68%) received fosfestrol as the second line of treatment after progression on complete androgen blockade, 14/47 (30%) received it as the third line, and 1/47 received it as the fourth line of treatment. The median prostate-specific antigen (PSA) value at the start of fosfestrol and the nadir PSA value were 43.7 ng/ml and 13.1 ng/ml, respectively. Ninety-one percent (n = 43) of patients had not been previously treated with chemotherapy (docetaxel). Response of PSA of >50% was observed in 55% (n = 26) of patients. The median EFS and median OS after the start of fosfestrol were 6.8 and 14.7 months, respectively, with a median follow-up of 10.9 months. Only two patients developed Grade 3 toxicity, both of whom had diarrhea. Conclusions: In resource-challenged settings, oral fosfestrol is an effective, cheap, and safe option for the management of metastatic prostate cancer progressing after first-line complete androgen blockade.
Keywords: Castration-resistant prostate cancer; diethylstilbestrol diphosphate; fosfestrol; prostate-specific antigen; survival